Contacts and Activities of the Latvia’s and Lithuania’s Roerich Societies in the “Theosophical Anti-Soviet Underground” in the 1940s: Based on the Materials of Latvian SSR MGB Case - Krėslinis, Uldis (Acta humanitarica academiae Saulensis, 2025)
On June 1, 1949, the Ministry for State Security of the Latvian SSR (LSSR MGB) initiated an investigation case, which within five months until October 29, 1949, grew into an accusation against fourteen persons for belonging to the “Theosophical anti-Soviet underground”. The members of the Latvian Roerich Society were accused and dissolved by the Soviet authority in 1940. However, they continued their activities illegally during the Nazi occupation and later the second Soviet occupation. MGB investigation paid special attention to the contacts of the “Theosophical anti-Soviet underground” outside Latvia, including the USA and Russia. However, especially close contacts since the 1930s united the followers of Nicholas Roerich’s ideas in Latvia with like-minded people in Lithuania. They continued their meetings and cooperation in the second half of the 1940s. This investigation case – almost simultaneously by similar charge the investigation against 18 persons happened in Lithuania – blaming prominent Latvian and Lithuanian intellectuals of distributing theosophical literature and of trying to preserve cultural values, was a vivid illustration of the Soviet regime policy to suppress any expressions of intellectual freedom. At the same time, this investigation case showed that the forms of society’s resistance to the repressive policy of authority were various, and among other forms and manifestations of resistance, there was another one: intellectual resistance. Its main specific features were following the broader, universal human values and, simultaneously, its ‘apoliticism’, not by choosing the “better” of the two occupying regimes, but by opposing the efforts of any political authority to restrict human freedoms and rights, and firstly – the freedom of thought. It is clear that at the level of whole nation, this intellectual resistance did not play a significant role – it was the resistance of an individual or narrow group of like-minded people, which can be partly explained as an “escape” from the existing political reality. However, judging by the sentences handed down by the court, this intellectual resistance in the eyes of the regime was not less dangerous as armed opposition.